FORMATION OF THE RUSSIAN IDENTITY IN THE YOUTH ENVIRONMENT: EXPERIENCE OF PRACTICAL IMPLEMENTATION - Alina A. Levitskaya (Высшее образование в России, 2016)
The article addresses the experience of the North-Caucasian Federal University in the sphere of social formation of such personal qualities as all-Russian civil and civilizational identity, patriotism, culture of Russian oral and written speech, culture of interethnic and interfaith dialogue, legal culture, culture of social responsibility. These qualities are important for every young person irrelatively of training area. The author adduces the results of the surveys of young people in the North Caucasus Federal district conducted by a team of scientists of the North Caucasus Federal University and South scientific center of RAS (in the period 2009-2014) aimed at determination the «identity matrix» ofthe North Caucasian society.